Development of a liquid chromatography/mass spectrometry methodology to separate, detect, characterize and quantify PEG-resveratrol prodrugs and the conjugation reaction precursors and intermediates - Basavaraj, S.; Benson, Heather; Cruickshank, C.; Brown, David; Chen, Yan (John Wiley & Sons Ltd, 2011)
A simple and reliable liquid chromatography/mass spectrometry (LC/MS) method to monitor pegylation of resveratrol is described. The developed LC/MS method can separate and quantify unmodified MeO-PEG-OH, carboxylic acid terminated PEG, resveratrol and PEG-resveratrol prodrugs. This methodology was able to monitor and determine the extent of conversion of MeO-PEG-OH into respective acidic functional derivatives such as MeO-PEG succinylester acid (MeO-PEGO-SuccOH), which was found to be complete. The developed method was also utilised to determine the extent of conjugation of resveratrol to carboxylic acid terminated PEG. The conversion of carboxylic acid terminated PEG into a PEG-resveratrol conjugate was found to be 100% and 73%, respectively, for MeO-PEG succinylamide resveratrol (MeO-PEGN-Succ-RSV) and MeO-PEG succinylester resveratrol (MeO-PEGO-Succ-RSV). The 100% conjugation of MeO-PEGN-Succ-RSV is consistent with the result obtained from a nuclear magnetic resonance (NMR) study.The average molecular weights determined by LC/MS for MeO-PEG-OH, MeO-PEGO-SuccOH and MeO-PEGO-Succ-RSV were found to be 2108, 2321 and 2423 Da, respectively. These data correlate well with the theoretical values. This methodology proved to be simple and effective in determining the extent of functionalisation of PEG and its conjugation to resveratrol. Overall our LC/MS method coupled with NMR permitted complete characterisation of the polymeric prodrug pegylated-resveratrol and the reaction precursors.